Pengaruh Kualitas Produk, Harga dan Waktu Tunggu Terhadap Repurchase Intention Di Mie Gacoan Kota Palu - Misra; Syamsul Bahri Dg. Parani; Umar Syarifuddin; Setiawan Mandala Putra (Universitas Muhammadiyah Pontianak, 2026)
This study examines the influence of product quality, price, and waiting time on repurchase intention at Mie Gacoan Palu. Using a quantitative approach, data were collected from 100 consumers who had previously made repeat purchases through a questionnaire and analyzed using multiple linear regression. The results show that price and waiting time significantly affect repurchase intention, while product quality has no significant effect. Simultaneously, all independent variables significantly influence repurchase intention. These findings imply that maintaining competitive prices and improving service efficiency are more important in encouraging repeat purchases than relying solely on product quality. Keywords: Product Quality; Price; Waiting Time; Repurchase Intention; Consumer Behavior; Customer Satisfaction; Fast-Food Restaurant; Mie Gacoan